Physical Education in Pakistan (Fiep Bulletin - online, 2015)
Physical Education has received a great stimulus in Pakistan during the past decade. The Government College of Physical Education was started at Walton, Lahore, in 1950. The College is equipped with a modern Gymnasium, an open air swimming pool and grassy grounds. This place is Blessed with Fresh air and is free from the smoke of the factories.